An All‐Fluorinated Electrolyte Toward High Voltage and Long Cycle Performance Dual‐Ion Batteries (Adv. Energy Mater. 19/2022). Issue 19 (19th May 2022) - Wang, Yao; Zhang, Yanjun; Dong, Shuyu; Zhou, Wenchong; Lee, Pui‐Kit; Peng, Zehua; Dang, Chaoqun; Sit, Patrick H.‐L.; Guo, Junpo; Yu, Denis Y. W.
Abstract : Dual‐Ion Batteries In article number 2103360, Denis Y. W. Yu and co‐workers report the development of an all‐fluorinated electrolyte which enables highly reversible PF6 − and Li + storage towards high performance dual‐ion batteries (DIBs). Because of its high‐power capability, the DIB is suitable for modulating power supply and the demands of renewables, and for fast‐charging of electric buses within minutes.